Responsibility and liability in emergency management to natural disasters: A Canadian example. (June 2016) - Raikes, Jonathan; McBean, Gordon
Abstract: Most provincial emergency management legislation (Quebec excepted) fails to include regulatory guidelines as to how local authorities reduce community vulnerability. This exposes individual(s) and groups to greater vulnerability to disasters if the local authority decides not to act or provide inadequate management. In addition, access to financial resources to assist or compensate local governments and/or private landowners for damages endured often come with attachments or do not exist. When damages result from a government's action or inaction in the event of an emergency, provisions in provincial legislation and court findings have reduced government exposure to civil liability at common law further exposing private landowners to financial risk. This paper argues that a lack of standards in emergency management legislation, restrictive access to financial assistance and/or compensation and reduced government exposure to civil liability at common law expose private landowners to greater vulnerability to disasters and the liability attached. It is essential that those responsible for proactive/preventative planning for disasters work from a standard playbook, one which sets minimum safeguards for the public. Absent of clear and fulsome compensation guidelines, private landowners will bear an unfair and disproportionate financial risk.